Effect of foliar spray with different concentration of nitrogen and phosphorus fertilizers on growth and yield of tomato C.V (Roma) - بريسم, ترف هاشم; أبو الميخ, محمد طرخان; عاصي, صباح لطيف (Journal of Kerbala for Agricultural Sciences, 2016)
This experiment was conducted in the Hort.Res. Station on a silty clay loam soil to study the effect of the interaction of the concentration of N and P(0, 0.15,0.30,0.60%) on growth and yield of tomato plants by Using RCBD with three replication. Results showed that a significant increase of dry matter 10.60% was observed at 0.6% N. Yield on the other hand fallowed the same was 31.30% at 0.6% p while the P showed the same trend regards the yield and the highest percent reached 34.90% In the fruit there was an obvious increase of N and P content 54.20%and 50% respectively .As for the interaction, the treatment of 0.3% N and 0.6% P resulted in higher percent 37.84% , 31.61 % in the dry matter and yield respectively .